The implementation of the Leader programme in Central Europe: Between a local development approach and political instrumentalisation - Chevalier, Pascal; Dedeire, Marc; Kovács, Dezső; Póla, Péter (Discussion Papers, 2013)
Over the course of the last thirty years, the rural development paradigm in the European Union, albeit at different rates and according to different processes in individual countries, evolved significantly. A paradigm of agricultural development based on intensification and modernisation reflecting the tenets of a productivist model has gradually been replaced by a new paradigm in which rural development is integrated, sustainable and, above all, local (Cork Declaration, 1996). Having emerged in the 1970s and been institutionalised in the 1990s by means of the Leader European Initiative Programme, a new model of local development founded on a bottom-up approach to the valorisation of local resources and the involvement of new actors in the elaboration and implementation of strategies began to emerge. This policy initiative, based on a territorial, rather than a sector-based approach, implies a new way of thinking about territorial development – originally founded on a centralised, exogenous model – which takes into account a more endogenous perspective involving new forms of governance. It also implies a new way of thinking about power by encouraging partnerships between local authorities armed with additional rights and responsibilities, and new actors from local associative and entrepreneurial spheres. In Central Europe, in countries still marked by the influence of centralised political traditions and a sometimes partial, incomplete re-establishment of the autonomy of local authorities (communes, micro-regions, regions, etc.), this transition, perhaps here more than elsewhere, implies a reappraisal of local powers, partnerships and territories providing a platform for new local development projects. Emanating from a combination of EU and domestic policies and, above all, bottom-up initiatives launched by local political actors and new social subjects participating in local development projects (project leaders, enterprises, structured groups, associations, etc.), new structures have emerged in Central Europe, some of them characterised by new forms of governance. Using the results of an analysis of the implementation of the Leader Programme in Lithuania, the Czech Republic and Hungary, we will look at how the European local development model is received and applied in Central Europe. Can we really talk about a bottom-up approach in line with the philosophy of local development? To what degree are these territories capable of elaborating and initiating development projects? Is it simply a question of national governments imposing upon local territories and instrumentalising local development?